Nutritional Aspects of Three Termitomyces and Four Other Wild Edible Mushroom Species from Sri Lanka - Gunasekara, Niranjan; Nanayakkara, Chandrika; Karunarathana, Samantha; Wijesundera, Ravi (Chiang Mai University, Faculty of Science, 2021)
Species of Termitomyces are considered as a group of prime edible mushrooms owing to their unique meaty flavour and texture. Nutritional composition data of some species in this genus are scanty due to their rare and seasonal nature. On the other hand, the nutritional value of many Sri Lankan wild edible mushrooms remained unexplored. Therefore, proximate, mineral, fatty acid, amino acid, and free sugar compositions of T. eurrhizus, T. heimii, T. microcarpus, together with four other wild edible mushrooms (Auricularia sp., Lentinus squarrosulus, Pleurotus djamor and Schizophyllum commune) were investigated. Proximate and mineral compositions were examined using the Association of Official Analytical Chemists (AOAC) official methods. The fatty acid, amino acid and free sugar compositions were determined using chromatographic methods. Studied mushrooms showed 8.54-31.05% of crude protein, 1.21-12.35% crude fat and 22.81-69.13% available carbohydrate percentages on a dry weight basis (DW). The fraction of unsaturated fatty acids was over 60% of the total fatty acids and oleic acid was the major fatty acid. Total amino acid content varied between 0.80-6.87% DW and glutamic acid was the most abundant. Trehalose was the major sugar, and the content of glucose was insignificant. Species of Termitomyces showed the highest protein and lowest carbohydrate contents. Essential amino acids/total amino acid and essential amino acids/non-essential amino acids ratios of Termitomyces spp.were closer to the values recommended by FAO/WHO. Thus, Sri Lankan Temitomyces spp. demonstrated better nutritional properties compared to the other wild edible mushrooms included in the study
Keywords: wild edible mushrooms; Termitomyces; Nutritional composistion